The Pam18/Tim14–Pam16/Tim16 complex of the mitochondrial translocation motor: The formation of a stable complex from marginally stable proteins - Iosefson, Ohad (Cold Spring Harbor Laboratory Press, 2007)
The vast majority of mitochondrial proteins are imported from the cytosol. For matrix-localized proteins, the final step of translocation across the inner membrane is mediated by the mitochondrial translocation motor, of which mhsp70 is a key component. The ATP-dependent function of mhsp70 is regulated by a complex, composed of a J-protein (called Pam18 or Tim14) and a J-like protein (called Pam16 or Tim16), and the nucleotide exchange factor Mge1. In this study, we investigated the structural properties of a recombinant purified Pam18/Tim14–Pam16/Tim16 complex using cross-linking with the bifunctional reagent DSS and CD-spectroscopy. The results of the study show that both Pam18/Tim14 and Pam16/Tim16 are thermally unstable proteins that unfold at very low temperatures (T(m) values of 16.5°C and 29°C, respectively). Upon mixing the proteins in vitro, or when both proteins are co-overexpressed in bacteria, Pam18/Tim14 and Pam16/Tim16 form a heterodimer that is thermally more stable than the individual proteins (T(m) = 41°C). Analysis of the properties of the complex in GdnHCl shows that dissociation of the heterodimer is the limiting step in achieving full denaturation.